Evaluating the Power Systems Reliability by Developing Reliability Network Equivalent Techniques - MohammadReza Zare; M Iranpour (Majlesi Journal of Electrical Engineering)
due to the importance of providing reliable electricity for consumers in todayâs power networks, the need for studies in the field of power systems reliability is feeling increasingly considering inherent uncertainties of renewable sources. Therefore, the main challenge of this study is to provide an efficient technique for evaluating reliability of power systems considering economic transactions between generative companies and load sources and review the impact of renewable sources on system reliability. In this article, a solution is improved based on equivalent techniques of power system reliability considering the effect of changes in wind speed for producing wind power in the network. In addition, a new method has been provided for reliability assessment of transmission network to check the adequacy of transmission lines corresponding to each load point based on the maximum power that can be transferred. In this study, we have avoided to do iterative calculation for computing adequacy of transmission lines in load point indices when the load and generation level are variable. Finally, RTS IEEE is used as the sample network in order to evaluate the efficiency of the proposed algorithm. The results indicate the high efficiency of the proposed method for reducing reliability of computation time. uncertainty of renewable sources, reliability, bilateral contracts, network equivalent techniques